Induction of Cellular DNA Synthesis by the Nondefective Adenovirus 2-Simian Virus 40 Hybrid Viruses - Schnipper, Lowell E. (1973)
Induction of cellular DNA synthesis by the nondefective adenovirus 2-simian virus 40 hybrid viruses was examined in monkey and hamster cells. It was not possible to discriminate the effects of the hybrid viruses from those of wild-type adenovirus 2.